An Analysis of Educated and Uneducated-Mothers Toward Childrens’ Second Language Achievement in an Indonesian Rural Area - Jaleha Wael; Saidna Zulfiqar Bin Tahir; Abd Rahman (Fakultas Sastra - Universitas Muslim Indonesia, 2021)
Parents are the main person in charge of their children's education. Wherever the child undergoes education, both formal, informal and non-formal institutions parents still play a role in determining the future of their children's education. Education outside the family, not in the sense of releasing parental responsibility in children's education, but it is carried out by parents solely because of the limitations of knowledge owned by parents, because the nature of science that continues to develop following the development of the Times, while parents have limitations. The aim of this study is to analyze the influence of educated and uneducated mothers on the achievement of English language learning in an Indonesian rural junior high school. Data analysis in this study is qualitative based on the use of complete and in-depth information in interpreting data about variables, is non-quantitative and is intended to conduct in-depth exploration and not expand on phenomena. The method used is by interviewing, observation and documentation methods. The findings in this study, namely the role of parents in determining students' learning achievement in school was very large. Parents who did not pay attention to their child's education, for example they were indifferent to their child's learning process, do not pay attention at all to the interests and needs of their children in learning, do not manage their study time, do not provide or complete learning tools, do not want to know how the progress of learning, the difficulties experienced by the child in learning and others can cause children to lack or even not succeed in learning. Conversely, parents who always paid attention to their children, especially attention to their learning activities at home, made children more active and more excited in learning because the child knows that not only himself who wants to move forward, but his parents also have the same desire. So that the learning results or learning achievements achieved by students become better.